Cryptotanshinone reduces psoriatic epidermal hyperplasia via inhibiting the activation of STAT3. Issue 3 (8th March 2018) - Tang, Lipeng; He, Songmin; Wang, Xieqi; Liu, Hongying; Zhu, Ying; Feng, Bing; Su, Zuqing; Zhu, Wei; Liu, Bo; Xu, Fangfang; Li, Chutian; Zhao, Jie; et al.
Abstract: The discovery of new therapeutic drugs with the efficacious and safe ability to prevent epidermal hyperplasia is extremely urgent for psoriasis. Cryptotanshinone (CTS), an active component isolated from the root of Salvia miltiorrhiza Bunge, has been reported to have antibacterial and antitumor effects. However, its effects on psoriasis have not been reported. Here, we investigated the therapeutic effects of CTS on imiquimod (IMQ)‐induced psoriatic‐like skin model and explored the underlying mechanisms. Our results revealed that CTS effectively alleviates IMQ‐induced epidermal hyperplasia. In vitro studies also indicated that CTS potently inhibits the growth of keratinocytes. We further found that STAT3, a transcription factor for the cell growth, is the key mediator of CTS on the proliferation of keratinocytes. Taken together, our findings indicated that the curative effects of CTS on psoriasis are accomplished mainly through modulating STAT3, which providing evidences to develop CTS as a potential therapeutic agent for patients with psoriasis.